Monuments to Habsburg Rulers in the Former Crown Lands of the Habsburg Monarchy — Stages from Historicism to a Never-ending Story - Caroline Mang (Peristil, 2022)
In the compendium on the Vienna Ringstrasse, edited by Renate Wagner-Rieger, little mention is made of the sculptor Caspar Zumbusch and his Vienna School of Sculpture. The author outlines the emergence of the Viennese school of sculpture and the students of Caspar Zumbusch who came to Vienna from different parts of the monarchy. After the return to their own regions, they authored a number of monuments to Habsburg rulers. While many of these monuments were destroyed during various crises, especially after the collapse of the Monarchy, in the 20th and 21st centuries numerous examples were re-erected. Recently, several monuments to Habsburg rulers have even been reconceived and today again shape cityscapes in some of the former countries of the Habsburg Monarchy.